THE ROLE OF PROFESSIONAL TEACHERS IN IMPROVING EDUCATION - Fatik Lutviana Anggraini (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
Professional teachers play a fundamental role in implementing an effective and meaningful learning process. Teacher professionalism is not solely determined by pedagogical competence and mastery of material, but also by reflective, innovativeabilities, and integrity in carrying out educational duties. This study aims to comprehensively describe the role of professional teachers in learning and their contribution to improving the quality of the process and student learning outcomes. This study uses a literature review method with a descriptive-qualitative approach. The findings indicate that professional teachers act as learning designers, facilitators of educational interactions, managers of learning environments, and evaluators of learning outcomes. Teachers with high professional competence are able to develop contextual learning strategies, utilize technology adaptively, and implement a studentcentered approach. These roles have direct implications for the growth of learning motivation, active student involvement, and improved academic achievement